Evaluation of Mannheim peritonitis index to predict outcome of patients with hollow viscus perforation - Bamrah, Jotdeep Singh; Bhargava, Gopal Swaroop; Kohli, Manu (International Surgery Journal, 2020)
Background: Acute generalized peritonitis from gastrointestinal hollow viscus perforation is a potentially life-threatening condition. Mannheim peritonitis index (MPI) is a specific scoring system that facilitates early identification of patients with severe peritonitis for aggressive surgical approach and improved outcomes. Methods: A prospective observational study in 60 patients attending surgical emergency unit with perforation peritonitis was conducted to analyse the predictive capacity of MPI. MPI score was categorized into 3 groups: <21, 21 to 29 and >29. Data was compared for predicting mortality and morbidity. P value, chi square test and 95% CI were used as statistical tools. Results: Two thirds of 60 patients studied were younger than 50 years of age. Prognosis was poorer in patients above 50 years with age. 80% presented after 24 hours. Ileal perforation was the commonest etiology. Morbidity and mortality were worst in patients with MPI score >29. Conclusions: Mannheim peritonitis index is disease specific, easy to apply and effective scoring system predicting the outcome in perforation peritonitis, with increasing MPI score being directly proportional to higher mortality and morbidity of the patient.